Pemanfaatan E-Learning dalam Pembelajaran Seni Tari : Sebuah Tinjauan Literatur - Ola, Stefania Lidia (STKIP AGAMA HINDU SINGARAJA, 2024)
This article discusses the use of e-learning technology in dance learning through a comprehensive literature review. The research approach involves analysis of the successes and barriers to the use of e-learning technology, with a focus on increasing accessibility and student engagement. The research results show that e-learning technology has succeeded in increasing the accessibility and flexibility of learning, allowing students to access material anytime and anywhere. Interactive features such as videos and discussion forums also help increase student engagement in dance learning. However, barriers such as limited access and technological infrastructure, as well as challenges in integrating cultural aspects, require special attention. Limited access can create a digital divide, while cultural challenges highlight the need to maintain cultural values ​​in dance learning. In addition, this article identifies trends in the development of e-learning technology, such as the use of virtual reality (VR) and augmented reality (AR), which can enhance the learning experience by providing dance simulations and additional visual elements. Implications of the results of this research for dance learning practices involves efforts to increase the accessibility of e-learning technology, as well as the development of technology that is more sensitive to the cultural aspects of dance. In conclusion, the use of e-learning technology in dance learning provides significant potential, but attention needs to be paid to the challenges that arise to ensure effective implementation.